1998
DOI: 10.1063/1.477675
|View full text |Cite
|
Sign up to set email alerts
|

Response of the elastic properties of colloidal crystals to phase transitions and morphological changes

Abstract: We report on the shear modulus G of colloidal crystals formed from thoroughly deionized suspensions of charged latex spheres. G is measured as a function of particle number density n. Body- and face-centered-cubic (bcc and fcc) crystal structures are observed by simultaneously performed static light scattering, and a broad coexistence region is found between (2.7±0.1)×1018 m−3⩽n⩽(4.8±0.2)×1018 m−3. Below n=1019 m−3, G closely follows theoretical predictions for both bcc and fcc, while it stays constant through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
1
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 33 publications
2
60
1
1
Order By: Relevance
“…For both cases we could only obtain quantitative agreement if we reduced the reported colloidal charges considerably. For instance, if we set Z = 480 instead of the reported Z = 700 [8], we find that the bcc-fcc coexistence region extends from η = 0.0026 ± 0.0004 to η = 0.0045 ± 0.0001 at κ σ ≈ 0.45. This matches the 'salt-free' observations of [8] quantitatively.…”
Section: Results and Conclusionmentioning
confidence: 95%
See 2 more Smart Citations
“…For both cases we could only obtain quantitative agreement if we reduced the reported colloidal charges considerably. For instance, if we set Z = 480 instead of the reported Z = 700 [8], we find that the bcc-fcc coexistence region extends from η = 0.0026 ± 0.0004 to η = 0.0045 ± 0.0001 at κ σ ≈ 0.45. This matches the 'salt-free' observations of [8] quantitatively.…”
Section: Results and Conclusionmentioning
confidence: 95%
“…For instance, if we set Z = 480 instead of the reported Z = 700 [8], we find that the bcc-fcc coexistence region extends from η = 0.0026 ± 0.0004 to η = 0.0045 ± 0.0001 at κ σ ≈ 0.45. This matches the 'salt-free' observations of [8] quantitatively. Similarly, if we set Z = 350 instead of Z = 880 as reported in [5], the fluid-fcc coexistence is in the regime from η = 0.010 ± 0.005 to η = 0.030 ± 0.004 at κ σ ≈ 0.8, as observed experimentally in this low-salt regime [5].…”
Section: Results and Conclusionmentioning
confidence: 95%
See 1 more Smart Citation
“…These experiments include the ones made by Monovoukas and Gast [13], Sirota et al [14], and Schöpe et al [15]. What all three of them have in common is the observation of a broad gas-solid or solid-solid coexistence in the low-salt regime.…”
Section: Introductionmentioning
confidence: 99%
“…Both experiments and computer simulations have shown that low inter-particle repulsion and low volume fraction make colloidal crystals exhibit bcc structure and fcc structure is more favorable for higher repulsion and higher volume fraction. [37][38][39][40] For the five groups of PS particles investigated here, PS1 are bcc in the whole range of from 0.006 to 0.02. PS3, PS4, and PS5 which have larger effective charge exhibited fcc structures at the stable state, though bcc may be formed in the early stage of the crystallization process.…”
Section: B Influences Of Volume Fraction and Crystal Structure To D Expmentioning
confidence: 99%